2009
DOI: 10.1523/jneurosci.3336-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glycogen Synthase Kinase-3β Is Required for Hyperdopamine and D2Receptor-Mediated Inhibition of Synaptic NMDA Receptor Function in the Rat Prefrontal Cortex

Abstract: The interactions between dopamine and glutamate systems play an essential role in normal brain functions and neuropsychiatric disorders. The mechanism of NMDA receptor regulation through high concentrations of dopamine, however, remains unclear. Here, we show the signaling pathways involved in hyperdopaminergic regulation of NMDA receptor functions in the prefrontal cortex by incubating cortical slices with high concentration of dopamine or administering dopamine reuptake inhibitor 1-(2-[bis-(4-fluorophenyl)me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 123 publications
4
95
1
3
Order By: Relevance
“…Our data show that activity-dependent LTD of EPSC NMDA at the hippocampal-PFC synapse relies on endogenous activation of D2Rs. This significantly extends the physiological relevance of previous studies demonstrating that activation of D2Rs by exogenous agonists can depress NMDA agonist currents or NMDA EPSCs (27,(31)(32)(33). In contrast to the report that in 9-10-mo-old mice only a subpopulation of PFC pyramidal neurons express D2Rs (34), we found that in every case tested, LTD was D2R-dependent.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our data show that activity-dependent LTD of EPSC NMDA at the hippocampal-PFC synapse relies on endogenous activation of D2Rs. This significantly extends the physiological relevance of previous studies demonstrating that activation of D2Rs by exogenous agonists can depress NMDA agonist currents or NMDA EPSCs (27,(31)(32)(33). In contrast to the report that in 9-10-mo-old mice only a subpopulation of PFC pyramidal neurons express D2Rs (34), we found that in every case tested, LTD was D2R-dependent.…”
Section: Discussionsupporting
confidence: 88%
“…Although we were not able to confirm a role for GSK3β (27) in the D2R-dependent LTD of EPSC NMDA , our results showing that the PKA inhibitor H89 depresses EPSC NMDA are consistent with a D2R-dependent inhibition of cAMP/PKA signaling being critical for (2,11.997) = 2.4; P = 0.13]. */**/*** = P < 0.05, P < 0.01, P < 0.001, respectively.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…[108][109][110] This is particularly intriguing since altered glutamate receptor functions have long been suspected to play a role in mental disorder pathology, mostly in schizophrenia. 73,111 However, it would be premature to conclude that the role of Akt-GSK3 signalling is restricted to the regulation of glutamate receptor functions.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, there have been considerable efforts by many groups to understand the cellular mechanisms of DA modulation in PFC neurons [49,50,[55][56][57][58][59][60]. Although the results of these efforts sometimes lead to contradictions and controversies, these studies from both in vivo and in vitro experiments have provided some principal features and mechanisms of DA modulation in the PFC circuitry [49].…”
Section: Pfc Receives Rich Monoaminergic Especially Dopaminergic (Damentioning
confidence: 99%